TINJAUAN YURIDIS HAK IMUNITAS PEJABAT NEGARA DALAM PENANGANAN PANDEMI COVID SEBAGAI ASPEK KRIMINOGEN TINDAK PIDANA KORUPSI: URIDICAL REVIEW OF THE IMMUNITY RIGHTS OF STATE OFFICERS IN HANDLING PANDEMIC COVID AS A CRIMINOGEN ASPECT OF CORRUPTION - Muhammad, Tio Aldino; Rusdiana, Emmilia (Universitas Negeri Surabaya, 2021)
The national legal policy has determined that Indonesia is a country that adheres to the Rule of Law system, as regulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia (hereinafter referred to as the 1945 Constitution). Mandated in Article 1 paragraph (3) Chapter I, the Third Amendment of the 1945 Constitution which returns that